Case of Extensive Polydactyly of Foot - R N Sharma (Indian Journal of Plastic Surgery)
A case of extensive polydactyly of the foot is being reported because of its rarity. The result of surgery has been satisfactory from cosmetic and functional points of view. A comparison with similar cases reported in the literature is included.